Gated Mesoporous Silica Nanoparticles Using a Double‐Role Circular Peptide for the Controlled and Target‐Preferential Release of Doxorubicin in CXCR4‐Expresing Lymphoma Cells. (17th December 2014) - de la Torre, Cristina; Casanova, Isolda; Acosta, Gerardo; Coll, Carmen; Moreno, María José; Albericio, Fernando; Aznar, Elena; Mangues, Ramón; Royo, Miriam; Sancenón, Félix; Martínez‐Máñez, Ramón
<x xml:space="preserve">Abstract</x> B‐cell non‐Hodgkin's lymphoma (B‐NHL) is the most frequent malignant lymphoid neoplasm, which has a high degree of relapse and chemoresistance. Thus, strategies to improve currently used therapies are needed. In this context, a new CXCR4‐targeted delivery system is described using mesoporous silica nanoparticles (MSNs) that are loaded with doxorubicin and capped with a derivative of the T22 peptide (P). This design makes full use of the great affinity of the T22 peptide to CXCR4 receptor, which is overexpressed in lymphoma cells. The peptide is able to guide the gated nanoparticle to B‐NHL cells to facilitate MSNs uptake via the CXCR4 receptor. The endocyted P‐capped MSNs are also opened by endosomal proteolytic enzymes to allow intracellular doxorubicin delivery.